A national survey of premedication for transfusion reactions in Japan. Issue 5 (October 2017) - Fujiwara, Shin-ichiro; Kino, Shuichi; Tanaka, Asashi; Hasegawa, Yuichi; Yokohama, Akihiko; Fujino, Keizo; Shigeyoshi, Makino; Matsumoto, Mayumi; Takeshita, Akihiro; Muroi, Kazuo; ,
Abstract: Background: Premedication before transfusion is commonly administered in clinical practice despite a lack of evidence for its efficacy. The aim of this study was to clarify the status of premedication and evaluate expert opinions regarding its use in Japanese medical institutions. Method: Between May and July 2016, we conducted a questionnaire survey on premedication before transfusion in 252 medical institutes that were certified by an academic society or employed transfusion experts. Results: A total of 141 institutes (54.2%) responded, and hematologists (n = 113) comprised the most frequent respondents. The purpose of premedication was to prevent urticaria, pruritus, and fever, and washed blood products were used for anaphylactic shock or refractory transfusion reactions before. Drugs for premedication were intravenously administered either just before or 30 min before transfusion. Both inpatients and outpatients were premedicated in a similar manner, and institutional guidelines were not established. More than half of the experts recognized premedication as efficient and necessary, and premedication for previous transfusion reactions was frequently implemented, particularly for platelet transfusion or in patients with hematological diseases. Some institutions administered one or more drugs for premedication from the first transfusion. Antihistamines and hydrocortisone were the most frequently used as premedication. Conclusion: Our study reports the current status of premedication for transfusion in Japan. Antihistamines and hydrocortisone were most commonly used for premedication despite a lack of evidence of their use. These findings may help clarify the indications for premedication and the use of washed blood products.